Penerapan Simulasi Monte Carlo untuk Pengukuran Value at Risk (VaR) - Ningsih, Setia; Arsal, Armayani (Research in the Mathematical and Natural Sciences, 2022)
The purpose of this study was to determine the measurement of value at risk (VaR) in Islamic stocks using the Monte Carlo simulation. The population used in this study are companies whose shares are listed on the Jakarta Islamic Index (JII). For the selection of samples using purposive sampling with the criteria of selecting companies engaged in the mining sector, namely ADRO, ANTM, INCO and PTBA. The results showed that the difference in VaR values ​​in each replication was caused by differences in the results of each simulation carried out, but the results were not different. far from each other because the parameters used in the simulation are the same. Therefore, in order to stabilize the results, the average value of the resulting VaR is taken. Based on the calculation results, the average value obtained is Rp. 1.132.721 at a 95% confidence level in a period of one day.